Fuzzy Comprehensive Evaluation of Human Work Efficiency in a High-Temperature Thermal-Radiation Environment - Zhai, Yingni; Wang, Xinta; Niu, Haobo; Wang, Xianglin; Nie, Yangwen; Huang, Yanqiu (Sustainability, 2022)
Work efficiency is not only related to objective cognitive performance, but it is also closely related to subjective psychological feelings. The existing research mostly focuses on the human safety tolerance limit from the physiological perspective, and there are few studies on work efficiency. In order to evaluate the work efficiency of humans in a high-temperature thermal-radiation environment, this paper proposes a method of personnel work efficiencies evaluation based on the fuzzy comprehensive evaluation method. In this method, the objective cognitive ability and subjective questionnaire data of human subjects in a thermal-radiation environment were obtained by building a high-temperature thermal-radiation platform, and the ergonomic status score (ESS) was calculated to determine the work efficiency evaluation grade. The results of this study indicate that subjective job satisfaction has a strong influence on work efficiencies. The safe WBGT temperature threshold that can be borne by personnel in a high-temperature thermal-radiation environment is lower than that in a single high-temperature environment. The ergonomic status score decreased significantly with the increase of radiation temperature. When the radiation temperature is 300 °C (WBGT temperature ≥ 33.2 °C), the work should be stopped immediately to ensure the safety and health of personnel. The research results can provide a reference for labor protection in high-temperature working environments.